Soviet relations with the Zionist entity from 1967-1972 - محفوض زين الدين; علاء الدين إبراهيم; عمران خضر (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research begins to clarify the role of the Soviet Union in the events during the research period, most notably the 1967 war, by studying its relations with the Zionist entity in that period. The framework of its goals and principles in supporting liberation movements and the rights of peoples in themselves and getting rid of the yoke of Western imperialism accordingly, he supported the Arab peoples with money, weapons, and the Zionist entity returned them. It took the Union as well as the Soviet to cut off relations with this entity, But the Zionists harnessed all their energies to pressure the Soviets regarding the issue of Jewish immigration, and they succeeded to some extent, especially in light of the period of peaceful coexistence adopted by Nikita Khrushchev, where he tried to rapprochement with the West and end the policy of constant- tension, and Soviet politicians began to try to get closer to the Zionists to soften the relation with The United States of America, the Zionists took advantage of that goal in the immigration file.